Kriminalisasi Nelayan Tradisional dalam Perspektif Human Security: Studi Kasus Perbatasan Maritim Indonesia–Malaysia di Selat Malaka - Sepgia Tonglo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The criminalization of traditional fishermen in the Indonesia–Malaysia maritime border region is an issue that highlights the tension between asserting national sovereignty and protecting coastal communities. Traditional fishermen who cross maritime boundaries are often categorized as engaging in illegal fishing and face various legal consequences, even though such violations frequently result from limited navigation technology, a lack of understanding of maritime boundaries, and economic pressures. This study aims to analyze the phenomenon of the criminalization of traditional fishermen in the Malacca Strait using a human security perspective. The method employed is descriptive qualitative research using a literature review approach, involving the collection of secondary data from scientific journals, official documents, reports from international institutions, and relevant legal sources. The results indicate that the criminalization of traditional fishermen is influenced by unclear maritime boundaries, limited access to navigation technology, vulnerable economic conditions, and suboptimal legal protection mechanisms for cross-border fishermen. From a human security perspective, this phenomenon is not only related to legal and national security aspects but also impacts economic security, individual security, and the security of coastal communities. Therefore, an approach more oriented toward human security is needed through enhanced bilateral cooperation between Indonesia and Malaysia, the provision of adequate navigation technology, public awareness campaigns regarding maritime boundaries, and the strengthening of legal assistance for traditional fishermen. In this way, maritime border management can be carried out more fairly and humanely without neglecting national sovereignty interests